Pengaruh Kompetensi Pegawai Terhadap Pengelolaan Arsip Statis Pada Dinas Kearsipan dan Perpustakaan. - Astia Hanunu; Rusli Isa; Melizubaida Mahmud (State University of Gorontalo, 2023)
This research employed a quantitative approach with a survey research method. The data used were primary data obtained from distributing questionnaires to the employees at the Office of Archives and Library of Gorontalo Province, with a total sample of 32 respondents. At the same time, the data analysis technique used was simple linear regression. The finding denoted that there was an effect of employee competency on the management of static archives at the Office of Archives and Library og Gorontalo Province. The effect of employee competency on the management of static archives was 45.3% while the remaining 54.7% was affected by other variables that were not examined in this research.